2010
DOI: 10.1111/j.1365-2303.2010.00776.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the performance of 100% rapid review using an average time of 1 and 2 minutes according to the quality of cervical cytology specimens

Abstract: The method of rapid review of 100% showed no difference in the detection of false-negative results using the time of 1 or 2 minutes. The quality of the sample did not influence the detection of false-negatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…A survey of 5,235 smears considered negative at the first selection used 100% RR at different times of counting, and detected 88 cases suspected of positivity, 45 of which were independently confirmed after cytological diagnosis [12]. Another study with 2,500 cytological tests considered negative after 100% RR detected 310 suspected cases, with 140 established after histopathological analysis [21], which could be used as an IQC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A survey of 5,235 smears considered negative at the first selection used 100% RR at different times of counting, and detected 88 cases suspected of positivity, 45 of which were independently confirmed after cytological diagnosis [12]. Another study with 2,500 cytological tests considered negative after 100% RR detected 310 suspected cases, with 140 established after histopathological analysis [21], which could be used as an IQC.…”
Section: Discussionmentioning
confidence: 99%
“…After this rapid review (RR) all suspect smears are subjected to a detailed review to define a final diagnosis [11]. This method is known to be used as a tool for internal quality control (IQC) in the UK and in other European countries, Australia, and in North America 100% RR is also used in quality assurance in cytopathology [11, 12]. …”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of rapid prescreening was approximately 60% higher than that of 100% rapid review in detecting abnormalities as severe as ASC-US or worse, and although no other studies have yet been carried out to compare these methods, these findings are in agreement with other studies that have evaluated rapid prescreening and 100% rapid review separately. 3,4,9,19,20,[28][29][30][31][32] Significant improvement in sensitivity was found in routine screening following implementation of rapid prescreening and 100% rapid review as methods of internal quality control. Sensitivity increased 24% and 15% for rapid prescreening and 100% rapid review, respectively, in detecting abnormalities as severe as ASC-US or worse.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, various studies have confirmed the better performance of this technique in detecting false-negatives, in comparison to R-10% and clinical risk criteria [3,7,12,13,14,15]. …”
Section: Introductionmentioning
confidence: 99%